Ethnobotanical, phytochemical and pharmacological aspects of Bengal Pogostemon (Pogostemon benghalensis) - Sangeeta Dahiya; Daizy R. Batish; Harminader Pal Singh (Shahrekord University of Medical Sciences, 2020)
Pogostemon benghalensis (Burm.f.) Kuntze (Lamiaceae) is an important aromatic plant. Multiple classes of phytochemicals such as flavonoids, phenols, phytosteroids, carbohydrates, fatty acids, glycosides, sterols, terpenoids, tannins, essential oil, and alkaloids have been isolated from the title species. Different plant parts have been used as traditional remedies for various ailments. The present review aims to update and coherent the fragmented information on botanical aspects, phytochemistry, traditional uses, and pharmacological activities. An extensive review of the literature was carried out by using various search engines like PubMed, Scopus, Science Direct, Google Scholar, Google, Scifinder for information. The articles were searched using the keywords "Pogostemon", "Parviflorus', "benghalensis". Chemical structures of the chemical compounds were drawn using software Chem Draw ultra 8.0. Most of the plant parts have been used for the treatment of various ailments. Phytochemistry reveals that the plant is a rich source of various biologically active compounds. Pogostemon extracts exhibited numerous pharmacological effects like anticancer, anti-inflammatory, antimicrobial and antioxidant activities. In sum, P. benghalensis is a promising aromatic and medicinal plant as depicted by its various traditional uses and pharmacological studies. Bioactive compounds, responsible for its various pharmacological activities at the molecular level, need further detailed investigations. Future clinical studies are also required to validate the various traditional uses of P. benghalensis.